A Dual Process Model of Attitudes towards Immigration: Person × Residential Area Effects in a National Sample. Issue 4 (24th January 2013) - Sibley, Chris G.; Duckitt, John; Bergh, Robin; Osborne, Danny; Perry, Ryan; Asbrock, Frank; Robertson, Andrew; Armstrong, Gavin; Wilson, Marc Stewart; Barlow, Fiona Kate
<x xml:space="preserve">Abstract</x> This research took a person × situation approach to predicting prejudice by looking at how social worldviews interact with real‐world environmental factors to predict how people respond to immigrants within their local area. Taking a Dual Process Motivational approach, we hypothesized that a higher proportion of immigrants in the local community would be associated with negative attitudes toward immigration for respondents high in dangerous world beliefs. Conversely, we hypothesized that living in a highly affluent (as opposed to socioeconomically deprived) community would be associated with negative attitudes toward immigration for respondents high in competitive world beliefs. Both hypotheses were supported using regional information derived from national census data combined with representative survey data from a large telephone sample conducted in New Zealand (N = 6, 489). These findings support the proposition that individual differences interact with specific features of the environment to predict people's levels of prejudice in distinct ways.